THE ISSUE OF INTELLECTUAL INTUITION IN METAPHYSICS - Piętka, Dariusz (Studia Philosophiae Christianae, 2020)
The article presents problems of intellectual intuition in metaphysics from a semiotic point of view. There are various types of intuition in philosophy: rational intuition, irrational intuition, and sensual intuition. All of them are immediate ways of cognition. Classical metaphysics uses intellectual intuition as its main method to find out and justify its statements. The main problem of intellectual intuition is an intersubjective approach to the object of metaphysics. The main aim of this paper is the objectivization and rationalization of intellectual intuition in language. The semantic notion of meaning and the pragmatic notion of understanding are the fundamental tools which are used to translate the issue of intuition from the subject-ma$er level into the language level. This operation allows to look at intuition in a non-psychological manner. It enables the objectivization of the method of intellectual intuition in the light of the understanding of meanings.